Fine-scale distribution of treeline trees and the nurse plant facilitation on the eastern Tibetan Plateau - Lyu, Lixin; Zhang, Qi-Bin; Deng, Xu; Mäkinen, Harri (Ecological indicators, 2016)
Above-average climate warming occurred during the 20th century in high altitude regions, and alpine treelines are believed to be an early indicator to respond to these warming-related changes. However, empirical investigations on treeline dynamics showed diverse results. The main objectives of this study are: (1) to investigate if treeline position shifted and if tree recruitment changed along with climate warming, and (2) to test if adult trees have “nursing effect” on tree establishment at treelines. We investigated two Balfour spruce (Picea balfouriana Rehd. et Wils.) treelines in Chang Niang (CNT) and Dang Dui (DDT), Dingqing county, Changdu prefecture, eastern Tibet. At each treeline site, three replicate plots with a size 30m×50m were established. The coordinates of each tree within the plots were recorded and the age of each tree was identified by dendrochronological method. The changes in treeline position and tree recruitment were examined from spatially fine-scale distribution of trees and their age structure. The spatial patterns of individual trees were analyzed to infer the neighborhood effects. Results indicate that plots CNT2, CNT3, DDT1 and DDT2 showed stable treeline position during the last century, whereas plots CNT1 and DDT3 showed treeline advancing movement. Tree recruitments in all the six plots were enhanced during the 20th century, with two peaks occurring in the 1890–1910s and the 1950–1990s. Seedlings and saplings showed a general clustered distribution in all the six plots. The diverse pattern of treeline movement and episodic regeneration suggest that the treeline activity is not merely a result of climate change. “Nursing effects” from adult trees may play an important role in shaping the treeline activities on the eastern Tibetan Plateau. Our findings reveal diverse patterns in treeline dynamics at a local scale and highlight the importance of incorporating biotic interactions into species distribution modeling approaches.